Effect of Limestone Powder as an Additive and as Replacement of Self-Consolidating Lightweight Foamed Concrete - Mohd Fauzi, Mohd Afiq; Muhd Sidek, Muhd Norhasri; Mohd Ridzuan, Ahmad Ruslan (International Journal of Sustainable Construction Engineering and Technology, 2020)
Concrete is the absolute most broadly utilized material in the development which must needs to guarantee attractive compressive quality and sturdiness. Mechanical properties of concrete are highly influenced by its density. A denser concrete generally provides higher strength. Numerous studies have been conducted for development of self-consolidating lightweight concrete (SCLWC) by investigating especially on their materials component and mix proportion. Commonly, considerations made by the researchers to produce SCLWC is by replacement of aggregates with alternative lightweight materials such as pumice, expanded clay, rubber granules and more or by adding foam agent. Besides, Limestone powder (LP) is one of concrete admixture that widely used as cement replacement. LP is proven can reduce energy consumption and resources from cement process, as well as effects the concrete properties. However, there are very few studies using only LP as main admixture for SCLWC. Therefore, the objectives of this study are to investigate the effect of limestone powder as an additive and as cement replacement in SCLW foamed concrete (SCLWFC) to the flowability and compressive strength. The experiment involves 3 types of SCLWFC which are normal mix; mixes without LP, additive mix; mixes with LP as an additive and replacement mix; mixes with and LP as cement replacement. Based on this study, the results indicated that the utilization of LP has positive effects to the flowability. Maximum value for slump flow was obtained when the LP as cement replacement at 40% and maximum value for compressive strength was obtained when the LP as an additive at 10%.